Kairo, Ägypten: Unterrichtsmaterialien zur ägyptischen Archäologie - Sigl, Johanna (e-Forschungsberichte des DAI, 2023)
Within the framework of the transformation partnership agreed upon between Germany and Egypt, a project was launced to develop teaching materials on the subject of ancient Egypt to increase the awareness of Egyptian children for the value of their cultural heritage. So far, three booklets on ancient Egyptian writing and scripts, mathematics and the so-called Turin Mining Papyrus have been published.